Roles of Melatonin in Goat Hair Follicle Stem Cell Proliferation and Pluripotency Through Regulating the Wnt Signaling Pathway - Zhang, Weidong; Wang, Niu; Zhang, Tongtong; Wang, Meng; Ge, Wei; Wang, Xin (Frontiers in Cell and Developmental Biology, 2021)
Emerging studies show that melatonin promotes cashmere development through hypodermic implantation. However, the impact and underlying mechanisms are currently unknown. In vitro study has previously demonstrated that melatonin induces cashmere growth by regulating the proliferation of goat secondary hair follicle stem cells, but there is limited information concerning the effects of melatonin on cell pluripotency. It is also known that Wnt signaling may actively participate in regulating cell proliferation and stem cell pluripotency. Therefore, in the current investigation, goat hair follicle stem cells were exposed to multiple concentrations of melatonin and different culture times to reveal the relationship between melatonin and the activation of Wnt signaling. A proportionally high CTNNB1 response was induced by 500 ng/L of melatonin, but it was then suppressed with the dosages over 1000 ng/L. Greater amounts of CTNNB1 entered the cell nuclei by extending the exposure time to 72 h, which activated TCF4/LEF1 and promoted the expression of the proliferation-related genes C-MYC, C-JUN, and CYCLIND1. Moreover, RORα and BMP4 were employed to analyze the underlying mechanism. RORα presented a sluggish concentration/time-dependent rise, but BMP4 was increased dramatically by melatonin exposure, which revealed that melatonin might participate in regulating the pluripotency of hair follicle stem cells. Interestingly, NOGGIN, which is a BMP antagonist and highly relevant to cell stemness, was also stimulated by melatonin. These findings demonstrated that melatonin exposure and/or NOGGIN overexpression in hair follicle stem cells might promote the expression of pluripotency markers NANOG, OCT4, and CD34. Our findings here provided a comprehensive view of Wnt signaling in melatonin stimulated cells and melatonin mediated stemness of goat secondary hair follicle stem cells by regulating NOGGIN, which demonstrates a regulatory mechanism of melatonin enhancement on the growth of cashmere.